O-228 How to introduce time-lapse technology in the IVF lab. (30th June 2022) - Ebner, T
Abstract: Although there is conflicting evidence on the actual clinical relevance of time-lapse technique (TLT) it is an add on technique that does come along with several advantages that would justify its use. However, once the decison has been made to go with TLT it has to be brought to mind that the European Tissues and Cells Directive dictates that new equipment is qualified accordingly before used routinely. This process is usually done according to GMP standards, e.g. a proper design qualification (DQ) would identify the most superior equipment which then undergoes further qualification steps such as installation (IQ), operational (OQ) and performance qualifications (PQ). The latter should involve a comparison with generally accepted laboratory KPIs, a process which would allow to establish levels of competence and aspirational benchmark. Upon proper qualification and clearance TLT can be an important tool in an existing quality management system, e.g. for evaluation of inter- and intraobserver variation, implementation of new consumables, and for testing the safety and efficacy of new lab methods.